Pembuatan Prakarya Ramah Lingkungan Melalui Pelatihan Ecoprint Teknik Pounding pada Forum Anak Desa (FAD) Prisma Pakeling Desa Wringintelu - Niken Pramesti Anindria; Dinda Febri Putri Thaher; Lavinia Tiara Malika; Moch Rizal Anwar; Dwi Wahyuningtyas (Universitas Muhammadiyah Manado, 2024)
Wringintelu Village, located in Puger District, Jember Regency, is a notable tobacco-producing area, facing significant challenges related to child involvement in hazardous work within the tobacco agriculture sector. The health risks for these children include Green Tobacco Sickness (GTS), alongside adverse effects on their education, such as school dropouts. To address this issue, a service program focused on ecoprint training was conducted by 16 students from Collaborative KKN #3 in partnership with the Wringintelu Village Children's Forum (FAD). The program aims to equip children with alternative skills through ecoprint training, using natural materials to produce handicrafts with marketable value, while reducing their reliance on tobacco-related jobs. The program's methods included socialization and hands-on ecoprint-making workshops, attended by 28 members of the FAD Wringintelu. This activity not only raises awareness of the dangers of working in the tobacco sector but also provides new skills that can support the economic sustainability of both children and their families. The participants' ecoprint products demonstrated market potential, offering safer and healthier economic opportunities. The success of this program highlights the importance of collaboration between communities and educational institutions, both formal and non-formal, in creating sustainable solutions to protect children from dangerous labor and support their rights optimally.